Share trading activity and the rise of the rentier in the UK before 1920*. Issue 6 (17th August 2020) - Acheson, Graeme G.; Coyle, Christopher; Jordan, David P.; Turner, John D.
Abstract: Using a hand-collected dataset, we examine share trading activity over the period 1882–1920 for the North British and Mercantile Insurance Company, one of the largest UK companies of the time. Our main finding is that the steady flow of rentiers into the shareholding constituency of this company stymied share trading activity. Another important finding is that share trading still occurred during the closure of the stock exchange in 1914, but on a much-reduced scale. We also find that there was a substantial boom in share trading and in insurance stock prices after World War I.